First record of the thread-legged assassin bug genus Proguithera from Japan, with description of a new species (Hemiptera: Heteroptera: Reduviidae) - Ishikawa, Tadashi; Naka, Takeru (Zootaxa, 2016)
The thread-legged assassin bug genus Proguithera Wygodzinsky, 1966 of the emesine tribe Leistarchini (Hemiptera: Heteroptera: Reduviidae) is recorded from Japan for the first time, and a new species P. kiinugama sp. nov., the third representative of this genus, is described based on specimens from Ishigaki-jima Island in the Ryukyu Islands. This new species can be distinguished from its congeners primarily by the absence of a median longitudinal sulcus on the anterior pronotal lobe, forewing with an incomplete cross vein connecting the M+Cu vein and a submarginal vein basad of the discal cell, and the anteroventral series of the profemur consisting of about 30 spine-like setae.